1989
DOI: 10.3758/bf03209805
|View full text |Cite
|
Sign up to set email alerts
|

Environmental control of morphine tolerance in the hamster

Abstract: Tolerance to morphine-induced hypoactivity in hamsters was investigated under conditions designed to test a Pavlovian conditioning model of morphine tolerance. One group of animals received i.p. injections of morphine (50 mg/kg) in the test environment and saline in the home cage; a second group received saline in the test environment and morphine in the home cage; a third group received saline in both environments. A subsequent morphine challenge in the test environment gave evidence of both associative and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…First, although unconditioned behavior pat-terns usually decrease across the session, increases (e.g., Montgomery, 1955) or bitonic functions have also been reported (Bindra & Spinner, 1958;Blanchard & Blanchard, 1971;Bronstein, Neiman, Wolkoff, & Levine, 1974;Chiszar, Wellborn, Wand, Scudder, & Smith, 1980;Davis & Astrachan, 1978;Schnur & Martinez, 1989; W. Thompson & Solomon, 1954). For example, Davis (1974aDavis ( , 1974b reported that startle responses elicited by a tone decreased with successive tone presentations when the tone was 120 dB, regardless of background noise.…”
Section: Unconditioned Behaviormentioning
confidence: 99%
“…First, although unconditioned behavior pat-terns usually decrease across the session, increases (e.g., Montgomery, 1955) or bitonic functions have also been reported (Bindra & Spinner, 1958;Blanchard & Blanchard, 1971;Bronstein, Neiman, Wolkoff, & Levine, 1974;Chiszar, Wellborn, Wand, Scudder, & Smith, 1980;Davis & Astrachan, 1978;Schnur & Martinez, 1989; W. Thompson & Solomon, 1954). For example, Davis (1974aDavis ( , 1974b reported that startle responses elicited by a tone decreased with successive tone presentations when the tone was 120 dB, regardless of background noise.…”
Section: Unconditioned Behaviormentioning
confidence: 99%
“…Accumulating evidence has emerged to suggest that learning processes play an essential role in the development of tolerance to the analgesic effect of opioids. For instance, a large amount of animal studies show that rodents administered with morphine in a distinctive context displayed a higher degree of morphine tolerance than the animals given morphine in a home cage (14)(15)(16)(17)(18)(19)(20). This associative opioid analgesic tolerance (AOAT) can also make a clinical impact on the analgesic efficacy in the treatment of patients with chronic pain (21).…”
Section: Introductionmentioning
confidence: 99%